Creativity Is Optimal Novelty and Maximal Positive Affect: A New Definition Based on the Spreading Activation Model - Schubert, Emery (Frontiers in Neuroscience, 2021)
Creativity is commonly defined as a process that leads to a novel and useful outcome (an idea, product, or expression). But two dilemmas about this definition remain unresolved: (1) A strict application of usefulness is difficult to apply to artistic works: Who decides what artwork is useful, and how it is useful? (2) The implied boundary conditions of novelty are problematic: The default perspective is that novelty has a monotonic increasing relationship with creativity, meaning that novelty can theoretically continue to increase to produce more and more creative outputs – a result that is not conceivable in practiceor it is categorical – i.e., novel or not. To address these dilemmas, this paper proposes a spreading activation model of creativity (SAMOC), a model built on a brain-architecture-inspired vast interconnected network of nodes, each node representing information, and assigned meanings through interaction with the environment. Nodes are linked to each other according to principles of temporal contiguity (linking objects/events in time) and similarity (linking objects/events by shared features). A node activated by attention spreads through the network through previously linked nodes. Nodes that are well connected activate each other easily, while those that are separated weakly connected (e.g., conceptually) do not. Net total activation corresponds to positive affect (e.g., pleasure), and this is proposed as an essential criteria for a creative work of art, instead of usefulness. And SAMOC also predicts that creativity will be optimised at an intermediate, not extreme, level of novelty. Too much activation will occur with combination of pre-existing ideas (hence reproduction rather than creativity), and too much novelty will lead not produce spread of to no activation spread. The two functions (spreading activation and the novelty curve) are superposed to demonstrate the this optimal novelty hypothesis. Early evidence of the hypothesis comes from the data that some great works of art were critically rejected at premiers (suggesting excessive novelty), but after sufficient repetition (and therefore linking) became suitably associated to commence generating activation. The hypothesis has important implications for future empirical research programs on creativity, and for the definition of creativity itself.